Nature of TiO2–oligonucleotides interactions by atomistic molecular dynamics simulations - Soria, Federico Ariel (2024)
We used molecular dynamics simulations to investigate the adsorption behavior of single-stranded deoxy-ribonucleic acid (ssDNA) segments on the anatase (101) surface. Four different ssDNA oligonucleotides, eachconsisting of six/twelve adenine (A6 and A12), six guanine (G6), six cytosine (C6) or six/twelve thymine (T6 andT12) nucleobases, were considered. We observed that the initial interaction between the ssDNA and the surfaceoccurs primarily through hydrogen bonding between the nucleobases and the surface, followed by strongchemical bonding between the terminal phosphate group and the anatase surface. The interactions between thenucleobases and the surface varied between the different ssDNA segments. Adenine showed the highest affinityfor the surface, whereas thymine showed the lowest affinity. In addition, the purine bases interact more stronglywhen the surface is negatively charged (as it would be at physiological pH) than in neutral surface (slightly acidicconditions), in agreement with experimental data from fluorescence experiments and ATR-FTIR spectroscopy.Moreover, our study provides mechanistic insights into the dynamic behavior of ssDNA on the anatase surfaceand comparative analyses on how different conditions (pH, fragment length, composition, etc.) affect DNA/TiO2interactions. Therefore, we expect that experimental scientists will benefit from our work in the design of optimalnanoconjugates for their specific final goals and applications.